Afferent Projections to Area Prostriata of the Mouse - Jin-Meng Hu; Chang-Hui Chen; Sheng-Qiang Chen; Song-Lin Ding; Song-Lin Ding (Frontiers Media S.A., 2020)
Area prostriata plays important roles in fast detection and analysis of peripheral visual information. It remains unclear whether the prostriata directly receives and integrates information from other modalities. To gain insight into this issue, we investigated brain-wide afferent projections to mouse prostriata. We find convergent projections to layer 1 of the prostriata from primary and association visual and auditory cortices; retrosplenial, lateral entorhinal, and anterior cingulate cortices; subiculum; presubiculum; and anterior thalamic nuclei. Innervation of layers 2-3 of the prostriata mainly originates from the presubiculum (including postsubiculum) and anterior midline thalamic region. Layer 5 of the prostriata mainly receives its inputs from medial entorhinal, granular retrosplenial, and medial orbitofrontal cortices and anteromedial thalamic nucleus while layer 6 gets its major inputs from ectorhinal, postrhinal, and agranular retrosplenial cortices. The claustrum, locus coeruleus, and basal forebrain provide relatively diffuse innervation to the prostriata. Moreover, Cre-dependent tracing in cortical areas reveals that the cells of origin of the prostriata inputs are located in layers 2-4 and 5 of the neocortical areas, layers 2 and 5 of the medial entorhinal cortex, and layer 5 of the retrosplenial cortex. These results indicate that the prostriata is a unique region where primary and association visual and auditory inputs directly integrate with many limbic inputs.